Biological strategies in aquaculture disease management: Towards a sustainable blue revolution - Keng Chin Lim; Fatimah Md Yusoff; Fatin M.I. Natrah; Mahanama De Zoysa; Ina Salwany Md Yasin; Jasmin Yaminudin; Murni Karim (Aquaculture and Fisheries)
Although the aquaculture industry has undergone monumental development worldwide, the ever-present threats of infectious diseases have become a constraining factor, imperiling its sustainability. Antimicrobial resistance (AMR) remains a real menace to industrial aquaculture due to the careless adoption of preventive therapies (antimicrobial therapeutic drugs) to forestall disease outbreaks in aquatic food production. Suitable strategies, or at least supplementary measures, should therefore be developed to curb the emergence and widespread transmission of AMR. Vaccination represents one of the primary options to substantially mitigate the economic damages imposed by emerging infectious diseases on global aquaculture; nevertheless, the availability of commercial aquatic vaccines is usually limited, and many vaccines only confer minimal or poor protection against infections (during the early stages of animal development). Accordingly, a large body of research has been enthusiastically exploring alternate approaches for managing animal health challenges. These efforts have led to the establishment of various biocontrol strategies, such as the versatile use of high-value functional ingredients (e.g., probiotics, prebiotics, synbiotics, paraprobiotics, postbiotics, and phytogenics), phage therapy, and quorum-sensing interference (QSI), to promote the health and welfare of farmed aquatic species in a responsive or preventative manner. This review article addresses the state-of-the-art pertinent to biological control as an eco-friendly green approach for aquatic disease management, paving the route to a sustainable blue revolution. The potential biological mechanisms of these strategies are also described, along with the impediments to scientific progress and topics that merit further investigation.